ORGANIZING WASTE THROUGH COMMUNITY PARTICIPATION IN NAPA VILLAGE - Dewi, Indah Kusuma (Jurnal Pengabdian Kepada Masyarakat MEMBANGUN NEGERI, 2020)
The community should be more aware of managing waste by sorting organic and non-organic waste and understanding how to manage Reuse Reduce Recycle (3R) Waste so that the waste problem in Napa Village can be overcome. The objectives to be achieved through community service and outreach activities are as follows: (1) To increase public awareness about the importance of waste management in Napa Village; (2) to find out the factors that become obstacles in waste management in napa village; (3) Increased understanding, community development efforts on the importance of preserving the environment; (4) Increased understanding of the community in efforts to foster institutions and professional societies in the face of modernization in their lives. The results obtained from the community service activities are: (1) Organizing waste in Napa Village is identification of problems related to waste management in Napa Village, socialization of the concept of 3R Trash, counseling on how to treat waste, surveying the location of waste disposal sites and identification of waste management institutions; (2) The concept of the implementation of waste management, namely the construction of temporary landfills/waste bins, the creation of the final landfill site for Napa Village, the establishment of the Napa Village Waste Management Institute, the provision of garbage transport equipment, the separation of waste with the 3R concept and the use of the 3R Waste Technology, with this activity the people of Napa Village no longer throw garbage in the sea, but in the place that has been provided.